The magic school bus and the electric field trip - Cole, Joanna; Degen, Bruce (New York Scholastic Press, 1997)
. Frizzle takes her class on a field trip through the town's electrical wires so they can learn how electricity is generated and how it is used
Hurg
5
Keywords: Electric power -- Juvenile literature; Electric power distribution -- Juvenile literature